Mortarboard Review - Jennifer D. Moss; Joel Parham (University of Kansas, 2023)
This article is the first in a series of planned reviews to be published annually that highlight a selection of dissertations. Some aspects of the selection and review methodology may be adjusted in coming issues as the process is refined to maximize the value to the field. Twenty-three Montessori-related dissertations completed during 2021 and 2022 were identified that represented five broad categories based on topic or subject matter. Two dissertations were selected for inclusion in this review because they represent high-quality research in areas that are of particular relevance and value to the field at this time: (a) public Montessori education and issues of equity and intercultural competence and (b) teacher perspectives and technology.